Peran Lembaga Keuangan Syariah Dalam Mengembangkan Bisnis Mikro dan Kecil di Indonesia - Alfiatun Zahara; Suci Mardiya; Bunga Andhini; Wahyu Febri Ramadhan Sudirman (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This study aims to analyze the role of Islamic microfinance institutions in developing micro and small businesses in Indonesia through the distribution of funds based on sharia principles. The method used is a literature review to identify how Islamic financing schemes, such as mudharabah and musyarakah, contribute to increasing access to capital for small business actors. The results of the study show that Islamic microfinance institutions provide more inclusive and fair financing and business assistance and management of social funds such as zakat, infaq, and sedekah. This supports the growth of micro and small businesses and improves the community's economic welfare. However, several challenges remain, such as low Islamic financial literacy and limited capital. Therefore, this study recommends the need for innovation in Islamic financial technology and increased public education to expand the reach and effectiveness of Islamic financial services for micro and small businesses.